Mitigation and aggravation at sentencing - Roberts, Julian V. (Cambridge : Cambridge University Press, 2011)
'This innovative volume explores a fundamental issue in the field of sentencing: the factors which make a sentence more or less severe. All sentencing systems allow courts discretion to consider mitigating and aggravating factors, and many legislatures have placed a number of such factors on a statutory footing. Yet many questions remain regarding the theory and practice of mitigation and aggravation. Drawing on legal and sociological perspectives and examining mitigation and aggravation in various jurisdictions, the essays provide practical illustrations of specific factors as well as theoretical justifications. After the foreword by Andrew von Hirsch, a number of contributors address broad conceptual issues raised at sentencing. These contributions are followed by several empirical chapters including an exploration of personal mitigation in English courts. The authors are leading scholars from a range of common law jurisdictions including England and Wales, the United States, Canada, Australia, New Zealand and South Africa'--
'Explicit guidance for sentencing decisions, and an explicit rationale to guide them, has been a notable feature of sentence-reform efforts over recent decades. In England and Wales, a system of sentencing guidelines is in place, based on statutory standards and guidelines provided by the Sentencing Council. Meanwhile, an extensive literature on sentencing theory has developed - for example, that based on notions of desert and proportionate sanctions, or on notions of'limiting retributivism' (see von Hirsch and Ashworth 2005FWD-003, chs. 9 and appendix 2)'--
Machine generated contents note: 1. Exploring aggravation and mitigation at sentencing Julian Roberts; 2. Re-evaluating the justifications for aggravation and mitigation at sentencing Andrew Ashworth; 3. The search for principles of mitigation: integrating cultural demands Allan Manson; 4. Personal mitigation at sentencing and assumptions about offending and desistance Joanna Shapland; 5. Intoxication as a sentencing factor: mitigating or aggravating? Nicola Padfield; 6. Beyond the partial excuse: Australasian approaches to provocation as a sentencing factor Arie Freiberg and Felicity Stewart; 7. Equality before the law: racial and social background factors as sources of mitigation at sentencing Kate Warner; 8. Personal mitigation: an empirical analysis in England and Wales Jessica Jacobson and Mike Hough; 9. Exploring public attitudes to sentencing factors in England and Wales Julian Roberts and Mike Hough; 10. The pernicious impact of perceived public opinion on sentencing: findings from an empirical study of the public's approach to personal mitigation Austin Lovegrove; 11. Addressing problematic sentencing factors in the development of guidelines Warren Young and Andrea King; 12. Proof of aggravating and mitigating facts at sentencing Kevin Reitz; 13. Mitigation in federal sentencing in the United States Will Berry; 14. The discretionary effect of mitigating and aggravating factors: a South African case study Stephan Terblanche.
Includes bibliographical references and index.
Includes bibliographical references and index.
Keywords: Sentences (Criminal procedure) -- England -- Congresses